2005
DOI: 10.1111/j.1464-5491.2005.01713.x
|View full text |Cite
|
Sign up to set email alerts
|

A T−786C polymorphism in 5′‐flanking region of the endothelial nitric oxide synthase gene and endothelium‐dependent arterial dilation in Type 2 diabetes

Abstract: The C allele of T-786C polymorphism of eNOS gene is a genetic risk factor for endothelial dysfunction in Type 2 diabetic patients, especially among smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…The rs2070744 SNP in the promoter region of eNOS has been observed in patients with vascular disease (Khurana et al, 2003;Rossi et al, 2003;Guang-Da et al, 2005), and this polymorphism inhibits the promoter activity of eNOS, reducing NO production in blood vessels and causing endothelial dysfunction (Brown et al, 2003;Kimura et al, 2003;Senthil et al, 2005). Previous studies have demonstrated a lack of consistent association between the rs2070744 polymorphism and recurrent pregnancy loss in Tunisians (Zammiti et al, 2008) and Koreans (Shin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rs2070744 SNP in the promoter region of eNOS has been observed in patients with vascular disease (Khurana et al, 2003;Rossi et al, 2003;Guang-Da et al, 2005), and this polymorphism inhibits the promoter activity of eNOS, reducing NO production in blood vessels and causing endothelial dysfunction (Brown et al, 2003;Kimura et al, 2003;Senthil et al, 2005). Previous studies have demonstrated a lack of consistent association between the rs2070744 polymorphism and recurrent pregnancy loss in Tunisians (Zammiti et al, 2008) and Koreans (Shin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review has indicated that rs1799983 may be correlated with recurrent spontaneous abortion (Su et al, 2011). The rs2070744 SNP has been observed in patients with vascular disease (Khurana et al, 2003;Rossi et al, 2003;Guang-Da et al, 2005); it inhibits the promoter activity of eNOS. However, whether rs2070744 is associated with RM remains controversial (Serrano et al, 2004;Shin et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Individuals carrying different single nucleotide polymorpisms of the eNOS gene have been shown to have significantly different vascular endothelial responses to environmental stimuli such as tobacco smoke [17][18][19], n-3 fatty acid intake [18], and exercise training [192]. The expression and activity of the p22phox gene, an important subunit of NADPH Oxidase (a major source of vascular reactive oxygen species) has been shown to be differentially affected by smoking and obesity based on the presence of the C242T single nucleotide polymorphism in this gene [207].…”
Section: Interaction Of Genetic Polymorphisms With Modifiable Lifestymentioning
confidence: 99%
“…While the exact sequence of events leading to the development of atherosclerosis is not clear, clinically apparent atherosclerosis is known to be preceded by homeostatic derangement of the vascular endothelium (the thin layer of cells that lines the lumen of blood vessels) [7]. Interestingly, suboptimal lifestyle choices have been shown to contribute *Address correspondence to these authors at the Department of Medicine, Cardiovascular Division and Pharmacology, Medical College of Wisconsin, 9200 W. Wisconsin Avenue, FEC Suite 5100, Milwaukee, WI 53226, USA; Tel: 414-456-6755; Fax: 414-456-6203; E-mails: mwidlans@mcw.edu; jiwang@mcw.edu to the development of this "endothelial dysfunction" [8][9][10][11][12][13][14][15][16], and genetic variations in key regulators of vascular endothelial function may dictate the relative impact of lifestyle choices on endothelial function [17][18][19]. This article will review the growing literature involving the effects of modifiable lifestyle choices on vascular endothelial function, the role of genetic variation play in modifying this risk, and the implications of these data for therapeutic recommendations and future study directions.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is first report associating the rs11771443 polymorphism in the promoter with PARDS. The rs2070744 SNP in the promoter region of eNOS has been observed in patients with vascular disease (Guang-da et al, 2005), recurrent miscarriage (Luo et al, 2013), and glaucoma (Liao et al, 2011). Therefore, our observations strongly suggest that this SNP could be a useful marker in the long-term monitoring of PARDS.…”
Section: Discussionmentioning
confidence: 99%